Adolescência em conflito com a lei: socioeducação no Paraná - Mocelin, Márcia Regina (2014)
The main topic of this thesis is the law conflict adolescents has and their policies. The focus is to analyze the institutions entitled Paraná Socioeducation Centers in regard to the coherence proposed by public policy between the educational reality of the institution and the real needs of these individuals for their reintegration into society. The proposed specific objectives are: define the educational policies in the socio-educational centers; understand the organization of the integral protection doctrine; the multiple determinations of the adolescents in law conflict and characterize socioeducation institutions historically. The established criterious methodology allows realize the adolescents in law conflict with all the contradictions which they live in. At the same time it contradicts itself, rising their history in to society. For this proposal, two fundamental categories were analyzed: Adolescents in Law Conflict and Socio-educational Public Policies in the light of historical-critical theory, identifying the theory effects in socio-educational assumptions. The scrutiny of documents, laws, service policy and the framework On the other side the practical part of this thesis reflections are also supported mainly by the author experience, participation and observation in this study field. Within this theoretical and methodological perception – the historical materialism - the methodology based in the historical critical theory proposes the problems overcoming, enabling the formation of a critical citizen, historic and transformer. The thesis is based mainly on the syntheses formulated by Karl Marx, Dermeval Saviani, Adolfo Sanchez Vazquez, Octavio Ianni, Karel Kosik, Alvaro Vieira Pinto, Antonio Carlos Gomes da Costa, Pavel Vasilievich Kopnin, Mario Alighiero Manacorda, Miguel Arroyo, Naura Syria Carapeto Ferreira. The thesis is systematized in the Introduction and four more chapters. The Chapter 2 ADOLESCENCES IN LAW CONFLICT analyzes how law conflict passes from teenager to teenager. Who is she/he? Where she/he comes from? What are the numbers in Brazil and in Paraná. In Chapter 3 CHILDHOOD AND ADOLESCENCE PUBLIC POLICY EDUCATION, deals with the educational policies history from the 90s, the historical adolescents in law conflict trajectory once called minor and a first approach to the ECA and the protection policy of the rights and duties of adolescents in law conflict. In Chapter 4 INTEGRAL PROTECTION DOCTRINE, the whole system of guaranteeing human rights and the teens in law conflict are treated analyzing the Integral Protection Doctrine which replaces the Doctrine of Irregular Situation. In Chapter 5 SOCIOEDUCATION, it presents the national system SINASE and its socioeducational policies. The social and educational measures, the Paraná policies by examining the IASP notebooks, the socio-educational programs and the Socioeducational Areas in Paraná are also presented. In SOME CONSIDERATIONS ABOUT HUMANIZATION SOCIOEDUCATION, dialogue on the humanization possibility by companionship for the possible emancipation and not young people stigmatization who at some point in their life became adolescents in law conflict. As reality has shown the public policy called Socioeducation System do not solve the juvenile delinquencies predicted on children educational rules V and VI of the Children and Adolescents Statute. Children and Adolescents Statute deals with the Semifreedom and the Deprivation of Liberty, once do not ensure the no criminal reincidence. In other words do not apply to reality which is intended. Furthermore the socioeducation do not guarantee the recovery of the adolescent offender.